Вплив високодисперсного кремнезему на проростання пшениці та стан води в її коренях - Turov, V. V.; Yukhymenko, E. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2011)
By 1H NMR spectroscopy in conditions of layer by layer freezing out of liquid phase the state of water in the roots of wheat, germinated in water or in the presence of nanoparticles of silica A-300 or the protective-stimulating composition based on methylated silica and mineral fertilizers were studied. It is shown that the residual water in the roots with a moisture content 7 wt% are present in the form of clusters of strongly and weakly associated water. Its characteristics vary significantly оn medium of germination. The maximum numbers of weakly associated forms of water are fixed for the roots germinated in the presence of nanosilica A-300. It is assumed that the presence of weakly associated forms of water causes the improvement in biometric parameters of wheat roots.